Inflation dynamics and exchange rate pass-through in Nigeria: Evidence from augmented nonlinear new Keynesian Philips Curve - Usman A. Bello; Aliyu Rafindadi Sanusi (CBN Journal of Applied Statistics, 2019)
This paper estimates a nonlinear augmented New Keynesian Philips Curve for Nigeria using the Smooth Transition Regression model for the period 1995Q1 to 2018Q2. The empirical evidence reveals the existence of two inflation regimes during the period under review. Food inflation, energy inflation, firms' marginal cost, and imported inflation account for most of the changes in the prices of composite consumers' basket in low exchange rate depreciation regime. However, the exchange rate solely explains price changes in the composite consumers' basket when inflation switches to high regime. Similarly, the results show that regime change in inflation is largely caused by exchange rate (transition variable) depreciation or devaluation of the naira. Furthermore, the paper finds that the threshold in exchange rate devaluation (depreciation) that triggers a regime switch from low to high inflation regime is about N75 relative to a dollar. The speed of regime switch was found to be significantly high at about 70% per quarter. The paper argues that achieving exchange rate stability is a necessary condition for disinflation during this regime. Therefore, this paper recommends that monetary policy response to low inflation regime must target the various components of the consumption basket while effort to curtail persistent high inflation must include a stable exchange rate of the naira.
Keywords: E12; E31; E52; E58; 330; Inflation; Regime switch; Philips curve; Threshold; Exchange rate